Colored wear-resistant composite coating for decoration and preparation method thereof

By forming a mixed oxide layer of TiO2 and Al2O3 on the surface of the titanium alloy substrate, and adopting a unique sintering process, the problem of difficult to take into account both the wear resistance and color effect of the oxide film in the prior art is solved, and a composite coating with high wear resistance and color durability is achieved.

CN119753571APending Publication Date: 2025-04-04FIYTA HOLDINGS LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411933088.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

When the prior art improves the wear resistance of the titanium alloy oxide film, it is easy to affect the color and multicolorability of the oxide film, resulting in a reduction in the appearance beautification effect.

Method used

A mixed oxide layer of TiO2 and Al2O3 is formed on the surface of the titanium alloy substrate by using a multi-target magnetron sputtering process. The main component of the base layer is Ti, and the surface layer contains 41% to 48% of Al2O3. The whole layer of γ-TiAl and α2-Ti3Al is formed through a unique sintering process.

Benefits of technology

It significantly improves the wear resistance and color durability of the TiO2 surface layer, maintains the bright color and multicolorability of the oxide film, and improves the hardness and bonding power of the composite coating. It is suitable for decorative functional parts that require high wear resistance and aesthetic effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753571A_ABST
    Figure CN119753571A_ABST
Patent Text Reader

Abstract

The present invention discloses a colored wear-resistant composite coating for decoration and a preparation method thereof, and belongs to the technical field of material surface treatment. The composite coating of the present scheme includes a base layer and a surface layer, the surface layer is a mixed oxide layer of TiO2 and Al2O3, and the main component of the base layer is Ti. Al2O3 has high hardness, excellent wear resistance and transparency, and can significantly improve the wear resistance and color durability of the TiO2 surface layer. The wear-resistant composite coating is prepared by a multi-target magnetron sputtering process, which not only simplifies the process flow, but also makes the coating composition easier to control. Through a unique sintering process, a full-lamellar structure of γ-TiAl and α2-Ti3Al is formed on the surface of the substrate, ensuring that the particle size and distribution of the mixed surface layer of Al2O3 and TiO2 are uniform and consistent. Through this scheme, a composite coating with a variety of color options can be prepared, which has good appearance effect, high hardness, good bonding force, and good wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material surface treatment, in particular to a colored wear-resistant composite coating for decoration and a preparation method thereof. Background Art

[0002] The surface of decorative functional parts, especially the appearance parts of jewelry products, has many performance requirements for materials such as wear resistance, corrosion resistance, scratch resistance, color, etc. Titanium alloy is one of the metal materials commonly used in many industries, and titanium alloy will show different colors after high-temperature oxidation at different temperatures, meeting the requirements of appearance designers. The reason why titanium presents different colors after high-temperature oxidation is that it forms a dense oxide film, which interferes with light and thus presents different colors. However, the oxide film of titanium is thin and easy to wear. Therefore, when it is applied to appearance parts, the surface often loses its bright color after wearing for a short time, and the appearance effect becomes darker and worse, which greatly reduces the favorability of consumers.

[0003] In the prior art, the wear resistance of the titanium oxide layer is mostly improved by doping other materials in the titanium oxide coating. The doped materials include polymer materials, silicone, etc. Such materials will affect the color and polychromaticity of titanium oxide, reduce the appearance beautification effect, and thus greatly reduce the product value.

[0004] Therefore, it is necessary to develop a colored composite coating that is wear-resistant and bright in color. Summary of the invention

[0005] The technical problem to be solved by the present invention is: in view of the above-mentioned defects of the prior art, a colored wear-resistant composite coating and a preparation method thereof are provided.

[0006] To achieve the above object, in a first aspect, the present invention provides a colored wear-resistant composite coating for decoration, the composite coating comprising a primer layer and a surface layer sequentially formed on the surface of a substrate, wherein:

[0007] The composition of the surface layer is 41% to 48% Al by mass percentage. 2 O 3 , the rest is TiO 2 ;

[0008] The primer layer contains at least Ti, the mass percentage of which exceeds 75%.

[0009] In the colored wear-resistant composite coating for decoration provided by the present invention, the thickness of the surface layer is 1 to 5 μm.

[0010] In the colored wear-resistant composite coating for decoration provided by the present invention, the thickness of the primer layer is 0.3-1 um.

[0011] In a second aspect, the present invention further provides a method for preparing a colored wear-resistant composite coating for decoration, wherein the colored wear-resistant composite coating for decoration as described above is prepared on the surface of a substrate, and the method comprises the following steps:

[0012] Step S1, using ultrasonic cleaning equipment to perform preliminary cleaning on the substrate, and then drying the substrate after cleaning;

[0013] Step S2, loading the ultrasonically cleaned substrate into a reaction furnace of a magnetron sputtering furnace, introducing an inert gas into the reaction furnace, and performing a secondary cleaning on the substrate;

[0014] Step S3, loading a first cathode target and a second cathode target in the magnetron sputtering furnace, and using the first cathode target and the second cathode target to deposit a base layer on the surface of the substrate that has been cleaned twice; the first cathode target and the second cathode target are both titanium alloys with a titanium content greater than 75%;

[0015] Step S4, loading a third cathode target and a fourth cathode target in the magnetron sputtering furnace, and using the third cathode target and the fourth cathode target to deposit a surface layer on the surface of the base layer, wherein the third cathode target is pure titanium and the fourth cathode target is pure aluminum; by controlling the power applied to the third cathode target and the fourth cathode target, the mass percentage content of Al in the surface layer is 38% to 45%;

[0016] Step S5, placing the substrate on which the base layer and the surface layer are deposited into a vacuum furnace, heating to a first temperature at a first heating rate after evacuation, keeping the temperature for a first time, and cooling according to a first cooling method; the first heating rate is 90°C / min to 120°C / min; the first temperature is 1200 to 1300°C, the first time is 1 to 3 minutes, and the first cooling method is first cooling to 750°C to 800°C at 80°C / min to 110°C / min, and then rapidly cooling to room temperature;

[0017] Step S6, placing the substrate cooled to room temperature into a heating furnace connected to air, setting the heating furnace to allow air to flow in at a first flow rate, heating to a second temperature at a second heating rate, and then keeping the temperature for a second time and then cooling according to a second cooling method; the first flow rate is 0.01m / s~2m / s, the second heating rate is 5℃ / min~15℃ / min, the second time is 0.5~2h, and the second cooling method is cooling to room temperature with the furnace.

[0018] In the method for preparing the colored wear-resistant composite coating for decoration provided by the present invention, in the step S1, the preliminary cleaning includes a wax removal solution cleaning step, an oil removal solution cleaning step, and a deionized water cleaning step performed in sequence.

[0019] In the method for preparing the colored wear-resistant composite coating for decoration provided by the present invention, in step S2, the vacuum degree in the reaction furnace is (8.0-15.0)×10 -3 Pa, the current of the cathode electron gun is 110-150A, the pulse negative bias voltage applied to the substrate is -350-500V, the working time is 10-15 minutes, and the inert gas is argon or nitrogen.

[0020] In the preparation method of the colored wear-resistant composite coating for decoration provided by the present invention, in the step S3, the vacuum degree in the reaction furnace is 0.1-1 Pa, the current of the cathode electron gun of the first cathode target and the second cathode target is 10-20 A, the pulse negative bias voltage applied to the substrate is -130--80 V, argon or nitrogen is introduced into the reaction furnace, the working time is 15-35 minutes, and the temperature in the reaction furnace does not exceed 200°C.

[0021] In the method for preparing the colored wear-resistant composite coating for decoration provided by the present invention, in the step S4, the vacuum degree in the reaction furnace is 0.01-0.3 Pa, and the current I of the cathode electron gun of the third cathode target is 纯钛 is 10-15A, the current I of the cathode electron gun of the fourth cathode target 纯铝 The pulse negative bias voltage applied to the substrate is -200 to -150 V, argon or nitrogen is introduced into the reaction furnace, the working time is 4 to 6 hours, and the temperature in the reaction furnace does not exceed 250°C.

[0022] In the method for preparing the colored wear-resistant composite coating for decoration provided by the present invention, in step S5, the vacuum degree in the vacuum furnace is maintained at 0.05-0.5Pa.

[0023] In the preparation method of the colored wear-resistant composite coating for decoration provided by the present invention, in the step S6, when the second temperature is 280°C to 330°C, a light yellow coating is obtained, when the second temperature is 370°C to 420°C, a dark gold coating is obtained, when the second temperature is 460°C to 530°C, a blue coating is obtained, when the second temperature is 570°C to 620°C, a green coating is obtained, and when the second temperature is 650°C to 690°C, a purple coating is obtained.

[0024] The present invention has the following beneficial effects:

[0025] The colored wear-resistant composite coating for decoration provided by the present invention comprises a base layer and a surface layer, wherein the surface layer is TiO 2 With Al 2 O 3 The mixed oxide layer of the base layer is mainly composed of Ti. Al 2 O3 It has high hardness, excellent wear resistance and transparency, and can significantly improve the performance of TiO 2 The wear resistance and color durability of the surface layer. The wear-resistant composite coating is prepared by multi-target magnetron sputtering process, which not only simplifies the process flow, but also makes the coating composition easier to control. Through a unique sintering process, γ-TiAl and α 2 -Ti 3 The full lamellar structure of Al ensures that 2 O 3 With TiO 2 The particle size and distribution of the mixed surface layer are uniform, which gives the oxidized composite coating the best appearance and excellent performance. Through this solution, a composite coating with a variety of color options can be prepared, with good appearance, high hardness, good bonding strength, and excellent wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0027] Figure 1 This is a schematic diagram of the structure of the multi-color wear-resistant composite coating of the present invention.

[0028] Figure 2 This is a schematic diagram of the steps of the method for preparing a multi-color wear-resistant composite coating according to the present invention.

[0029] Figure 3 Al in the coating surface layer B3 2 O 3 Schematic diagram of the final product when there is too much.

[0030] Figure 4 This is the Ti-Al binary phase diagram. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The colored wear-resistant composite coating provided by the present invention is used for the surface of decorative functional parts, especially the appearance parts of jewelry products, such as the surface of watch appearance parts such as watch cases, bezels, and watch straps, so that these appearance parts present colors such as light yellow, dark gold, and blue, and meet the requirements of wear resistance, corrosion resistance, and bio-friendliness. The colored wear-resistant composite coating provided by the present invention is also suitable for other appearance parts that need to meet the requirements of high hardness, wear resistance, corrosion resistance, and bio-friendliness.

[0033] like Figure 1 As shown, an embodiment of the present invention provides a colored wear-resistant composite coating for decoration, wherein the composite coating 20 comprises a base layer 21 and a surface layer 22 sequentially formed on the surface of a substrate 10, wherein:

[0034] The composition of the surface layer 22 is 41% to 48% Al by mass percentage. 2 O 3 , the rest is TiO 2 ;

[0035] The primer layer 21 at least contains Ti, the mass percentage of which exceeds 75%.

[0036] The present invention has no particular limitation on the thickness of the surface layer and the primer layer. In practical applications, the thickness of the surface layer and the primer layer is determined based on factors such as cost, efficiency, and durability.

[0037] In some embodiments of the present invention, the thickness of the surface layer 22 is 1-5 um.

[0038] In some embodiments of the present invention, the thickness of the base layer 21 is 0.3-1 um.

[0039] In some embodiments of the present invention, the thickness of the surface layer 22 is 1-5 um, and the thickness of the base layer 21 is 0.3-1 um.

[0040] In the embodiment of the present invention, the substrate refers to the watch case, watch strap, bezel, etc., and common materials thereof include 316L steel, 304 stainless steel, TC4 titanium alloy, etc.

[0041] TiO formed after oxidation of titanium alloy 2 The TiO2 layer is a bright and colorful coating. The principle is that when titanium is oxidized at different temperatures, an oxide film of different thickness will be formed on the surface. The films of different thickness will produce different interference effects on light, thus presenting various colors to meet the various color requirements of appearance designers. 2 It is thin, has poor wear resistance, and easily loses color due to wear.

[0042] To increase the TiO 2In the prior art, the wear resistance of TiO 2 Polymers, silicone, carbon fiber materials, etc. are added to the coating. However, this method often makes TiO 2 Color changes, loss of gloss, not suitable for applications requiring TiO 2 Therefore, in order to improve the TiO 2 The coating has good wear resistance and does not lose color. In the composite coating provided by the embodiment of the present invention, the final TiO 2 The surface layer contains a certain amount of Al 2 O 3 , Al 2 O 3 High hardness, good wear resistance and transparency, can greatly improve the TiO 2 The wear resistance and color durability of the surface layer do not affect the TiO 2 The base layer mainly composed of Ti is similar to the surface layer as a transition layer, and the two have a stronger bonding force, which can prevent the surface layer from peeling off; the TiO 2 and Al 2 O 3 It is corrosion-resistant, bio-friendly, and provides a good user experience.

[0043] However, if the Al in the final surface layer 2 O 3 If the content is too little and the particles are too small, the appearance will be whitish, affecting the color and gloss of the surface layer, and the wear resistance will be reduced; if Al 2 O 3 Uneven size and distribution will affect TiO 2 The uniform oxidation of the surface layer reduces the uniformity and saturation of the color, which greatly reduces the value of the product. 2 O 3 The proportion is 41% to 48%, and Al 2 O 3 and TiO 2 The particle size and distribution of Al 2 O 3 The particle size is 0.5-1.5um, TiO 2 The particle size of the particles is 1-2um. The finished product within the above particle size range can obtain a more ideal appearance visual effect.

[0044] like Figure 2 As shown, an embodiment of the present invention further provides a method for preparing a colored wear-resistant composite coating for decoration, wherein the colored wear-resistant composite coating for decoration as described above is prepared on the surface of a substrate, and the method comprises the following steps:

[0045] Step S1, using ultrasonic cleaning equipment to perform preliminary cleaning on the substrate, and then blowing the substrate dry after cleaning. The preliminary cleaning includes a wax removal solution cleaning step, an oil removal solution cleaning step, and a deionized water cleaning step performed in sequence.

[0046] In some embodiments of the present invention, the ultrasonic cleaning time is 5 to 7 minutes, the cleaning temperature is 50 to 60°C, and in the dewaxing solution cleaning step, the dewaxing solution ratio is dewaxing water: pure water = 1:8 to 1:16, and in the degreasing solution cleaning step, the degreasing solution ratio is degreasing agent: pure water = 1:15 to 1:30.

[0047] Step S2, loading the substrate cleaned by ultrasonic wave into a reaction furnace of a magnetron sputtering furnace, introducing an inert gas into the reaction furnace, and performing a secondary cleaning on the substrate.

[0048] The purpose of step S2 is to wash away the oxide layer on the surface of the substrate or impurities such as dust contaminated during the transfer of the substrate. In some embodiments of the present invention, in step S2, the vacuum degree in the reaction furnace is (8.0-15.0)×10 -3 Pa, the current of the cathode electron gun is 110-150A, the pulse negative bias voltage applied to the substrate is -350-500V, the working time is 10-15 minutes, and the inert gas is argon or nitrogen.

[0049] Step S3, loading the first cathode target and the second cathode target in the magnetron sputtering furnace, and using the first cathode target and the second cathode target to deposit a base layer on the surface of the substrate that has been cleaned twice; the first cathode target and the second cathode target are both titanium alloys with a titanium content greater than 75%.

[0050] In some embodiments of the present invention, in step S3, the vacuum degree in the reaction furnace is 0.1-1 Pa, the current of the cathode electron gun of the first cathode target and the second cathode target is 10-20 A, the pulsed negative bias voltage applied to the substrate is -130--80 V, argon or nitrogen is introduced into the reaction furnace, the working time is 15-35 minutes, and the temperature in the reaction furnace does not exceed 200° C. By controlling the working time, the thickness of the base layer can be controlled.

[0051] Step S4, loading a third cathode target and a fourth cathode target in the magnetron sputtering furnace, and using the third cathode target and the fourth cathode target to deposit a surface layer on the surface of the base layer, the third cathode target is pure titanium, and the fourth cathode target is pure aluminum; by controlling the power applied to the third cathode target and the fourth cathode target, the mass percentage content of Al in the surface layer is 38% to 45%, and the rest is Ti.

[0052] In the embodiment of the present invention, in step S4, the vacuum degree in the reaction furnace is 0.01-0.3 Pa, and the current I of the cathode electron gun of the third cathode target is 纯钛 is 10-15A, the current I of the cathode electron gun of the fourth cathode target 纯铝 The negative bias voltage applied to the substrate is 9 to 12A, the negative bias voltage applied to the substrate is -200 to -150V, argon or nitrogen is introduced into the reaction furnace, the working time is 4 to 6 hours, and the temperature in the reaction furnace does not exceed 250°C. By controlling the working time, the thickness of the surface layer can be controlled. By changing the current I of the cathode electron gun of the third cathode target 纯钛 and the cathode electron gun current I of the fourth cathode target 纯铝 , the content of Al and Ti in the base layer can be adjusted.

[0053] In the embodiment of the present invention, both the base layer and the surface layer are prepared by a multi-target magnetron sputtering process, which has a simple process flow and is easier to control the coating composition. The magnetron sputtering furnace can be equipped with 4 cathode target positions. When depositing the base layer, only the power corresponding to the first cathode target and the second cathode target is turned on, and when depositing the surface layer, only the power corresponding to the third cathode target and the fourth cathode target is turned on, which makes the control process simpler.

[0054] Step S5, placing the substrate with the bottom layer and the surface layer deposited thereon into a vacuum furnace, heating to a first temperature at a first heating rate after evacuation, and cooling in a first cooling manner after keeping the temperature for a first time; the first heating rate is 90°C / min to 120°C / min; the first temperature is 1200 to 1300°C, the first time is 1 to 3 minutes, and the first cooling manner is first cooling to 750°C to 800°C at 80°C / min to 110°C / min, and then rapidly cooling to room temperature. In the embodiment of the present invention, in the step S5, the vacuum degree in the vacuum furnace is 0.05 to 0.5 Pa.

[0055] The solution of the embodiment of the present invention is to obtain the final Al by heating and oxidizing in air. 2 O 3 With TiO 2 The mixed surface layer is to make the Al 2 O 3 The size and distribution are uniform, and the metallographic structure of the Ti-Al compound layer before oxidation should be γ-TiAl (hereinafter referred to as γ) + α 2 -Ti 3 Al (hereinafter referred to as α 2 ) full-lamellar organization. Because the organization is looser in the full-lamellar, all atoms can diffuse quickly between the lamellae. When heated to high temperature, α 2 The uniform oxidation of γ is not restricted, and the growth is fast, forming Al with relatively uniform size and distribution.2 O 3 / TiO 2 Mixed particles. But if the Ti-Al metallographic structure is near γ structure or γ+α 2 In the case of dual-state organization, the organization is not loose enough, and the diffusion speeds of atoms in different phases are relatively different. 2 It will be oxidized relatively first, and the γ atoms with slow atomic diffusion will be oxidized later, producing coarse TiO 2 and a large amount of fine Al 2 O 3 , a large amount of Al 2 O 3 The particles hinder the TiO 2 The rapid growth eventually forms oxidized particles of uneven size and distribution, such as Figure 3 As shown, the large particles are TiO 2 , small particles are Al 2 O 3 .

[0056] To obtain γ+α 2 To obtain a full lamellar structure, the sintering process of the Ti-Al compound layer needs to be controlled. Figure 4 As shown in the Ti-Al binary phase diagram, when the Al content is 38% to 45% (i.e. the final layer Al 2 O 3 When the temperature exceeds 1200℃, the Ti-Al compound is in the α single phase region, and then the α phase undergoes eutectoid reaction to generate γ+α 2 The lamellar structure of the lath; when the temperature is below 1200℃, the Ti-Al compound is in the α+γ dual phase region, and part of the α phase transforms into γ+α during cooling. 2 organization, obtain a large amount of γ plus a small amount of α 2 phase, and finally forms a near-γ structure or a dual-state structure. Therefore, in order to obtain γ+α 2 The best insulation temperature of step S5 is 1200° C. to 1300° C. When the temperature exceeds 1300° C., the performance of most base metal materials is easily damaged.

[0057] In the embodiment of the present invention, γ-TiAl+α 2 -Ti 3 The Al lamellar structure is formed to form Al with uniform size and distribution. 2 O 3 With TiO 2 The mixed surface layer makes the composite coating surface smooth and uniform after oxidation, has excellent visual effect, and has excellent wear resistance and corrosion resistance. In addition, because the surface layer of the present invention does not contain nickel, it is bio-friendly.

[0058] Step S6, placing the substrate cooled to room temperature into a heating furnace connected to air, setting the heating furnace to allow air to flow in at a first flow rate, heating to a second temperature at a second heating rate, and then keeping the temperature for a second time and then cooling according to a second cooling method; the first flow rate is 0.01m / s~2m / s, the second heating rate is 5℃ / min~15℃ / min, the second time is 0.5~2h, and the second cooling method is cooling to room temperature with the furnace.

[0059] In the embodiment of the present invention, in the step S6, the second temperature range is different, and the color of the obtained coating is different. Specifically, when the second temperature is 280°C to 330°C, a light yellow coating is obtained, when the second temperature is 370°C to 420°C, a dark gold coating is obtained, when the second temperature is 460°C to 530°C, a blue coating is obtained, when the second temperature is 570°C to 620°C, a green coating is obtained, and when the second temperature is 650°C to 690°C, a purple coating is obtained.

[0060] In the embodiment of the present invention, according to the appearance color of the product design, in step S6, the temperature is controlled accordingly to obtain a finished product with the expected appearance color. Because the appearance effects of different colors can be obtained by controlling the temperature, the solution of the present invention can meet a variety of personalized needs and has strong applicability.

[0061] The following three specific embodiments are used to describe in detail the method for preparing the colored wear-resistant composite coating for decoration of the present invention.

[0062] Example 1

[0063] In this embodiment, a wear-resistant, corrosion-resistant, and bio-friendly titanium oxide green composite coating is sputtered on a 316L steel substrate part. The specific steps are as follows:

[0064] Step S1, using a wax removal solution, an oil removal solution and deionized water in sequence to preliminarily clean the substrate in an ultrasonic cleaning device, and then blowing the substrate dry after cleaning.

[0065] Step S2, a magnetron sputtering furnace equipped with a cathode electron gun, an anode, a reaction furnace and an inert gas introduction device is used to perform secondary cleaning on the substrate that has been ultrasonically cleaned. Specifically, argon gas is introduced into the reaction furnace through the inert gas introduction device; the vacuum device is started to draw the vacuum degree in the reaction furnace to 12.0×10 -3 Pa, set the cathode electron gun current to 120A, the pulse negative bias to -350V, and the cleaning time to 12 minutes.

[0066] Step S3, in a magnetron sputtering furnace, two pure titanium cathode targets are used to deposit a base layer on the surface of the substrate. Specifically: argon gas is introduced into the reaction furnace through an inert gas introduction device; the vacuum pumping device is started to pump the vacuum degree in the reaction furnace to 0.5 Pa, the current of the cathode electron gun is set to 13A, the pulse negative bias voltage is -110V, the sputtering time is 25 minutes, and the temperature in the reaction furnace is 180°C.

[0067] Step S4, in a magnetron sputtering furnace, a pure titanium cathode target and a pure aluminum cathode target are used to deposit a surface layer on the surface of the base layer, and argon gas is introduced into the reaction furnace through an inert gas introduction device; the vacuum pumping device is started to pump the vacuum degree in the reaction furnace to 0.05 Pa, and the current I of the cathode electron gun corresponding to the pure titanium cathode target is set. 纯钛 The current I of the cathode electron gun corresponding to the pure aluminum cathode target is 15A. 纯铝 The current was 12A, the pulse negative bias voltage was -150V, the sputtering time was 5 hours, and the temperature in the reactor was 230°C.

[0068] Step S5, placing the parts with the deposited base layer and surface layer into a vacuum furnace, starting the vacuum pumping device, pumping the vacuum degree in the reaction furnace to 0.08 Pa, setting the vacuum furnace to start heating to 1200°C at a heating rate of 100°C / min, keeping the temperature for 2 minutes, first cooling to 750°C at a cooling rate of 80°C / min, and then quickly cooling to room temperature;

[0069] Step S6, put the parts cooled to room temperature into the heating furnace, set the air circulation rate of the heating furnace to 0.2m / s, and heat to 600℃ at a heating rate of 10℃ / min. After keeping warm for 1h, cool with the furnace to obtain the final finished parts.

[0070] The finished product was taken out, and the surface was green. The thickness of the composite coating was tested by scanning electron microscopy, and the test result showed that the thickness was about 2.5μm. The finished product was subjected to 24-hour salt spray and 48-hour artificial sweat tests, and there was no corrosion on the surface after the tests. The finished product was subjected to a wear resistance test in a vibration plate, and when the standard sample placed at the same time as the finished product was worn away by 6.0mg, the finished product had no obvious bottom exposure and discoloration.

[0071] Example 2

[0072] In this embodiment, a wear-resistant, corrosion-resistant, and bio-friendly titanium oxide blue composite coating is sputtered on a TC4 titanium alloy substrate part. The specific steps are as follows:

[0073] Step S1, using a wax removal solution, an oil removal solution and deionized water in sequence to preliminarily clean the substrate in an ultrasonic cleaning device, and then blowing the substrate dry after cleaning.

[0074] Step S2, a magnetron sputtering furnace equipped with a cathode electron gun, an anode, a reaction furnace and an inert gas introduction device is used to perform secondary cleaning on the substrate that has been ultrasonically cleaned. Specifically, argon gas is introduced into the reaction furnace through the inert gas introduction device; the vacuum device is started to draw the vacuum degree in the reaction furnace to 10.0×10 -3 Pa, set the cathode electron gun current to 150A, the pulse negative bias to -450V, and the cleaning time to 12 minutes.

[0075] Step S3, in a magnetron sputtering furnace, two pure titanium cathode targets are used to deposit a base layer on the surface of the substrate. Specifically: nitrogen is introduced into the reactor through an inert gas introduction device; the vacuum pumping device is started to pump the vacuum degree in the reactor to 0.3 Pa, the current of the cathode electron gun is set to 15A, the pulse negative bias voltage is -100V, the sputtering time is 20 minutes, and the temperature in the reactor is 200°C.

[0076] Step S4, in a magnetron sputtering furnace, a pure titanium cathode target and a pure aluminum cathode target are used to deposit a surface layer on the surface of the base layer, and nitrogen is introduced into the reaction furnace through an inert gas introduction device; the vacuum pumping device is started to pump the vacuum degree in the reaction furnace to 0.1 Pa, and the current I of the cathode electron gun corresponding to the pure titanium cathode target is set. 纯钛 The current I of the cathode electron gun corresponding to the pure aluminum cathode target is 13A. 纯铝 The current was 10A, the pulse negative bias voltage was -180V, the sputtering time was 6 hours, and the temperature in the reaction furnace was 200°C.

[0077] Step S5, placing the parts with the deposited base layer and surface layer into a vacuum furnace, starting the vacuum pumping device, pumping the vacuum degree in the reaction furnace to 0.15 Pa, setting the vacuum furnace to start heating to 1250°C at a heating rate of 110°C / min, keeping the temperature for 1.5 minutes, first cooling to 800°C at a cooling rate of 100°C / min, and then quickly cooling to room temperature;

[0078] Step S6, put the parts cooled to room temperature into the heating furnace, set the air circulation rate of the heating furnace to 0.5m / s, and heat to 500℃ at a heating rate of 5℃ / min. After keeping warm for 1.5h, cool with the furnace to obtain the final finished parts.

[0079] The finished product was taken out, and the surface was blue. The thickness of the composite coating was tested by scanning electron microscopy, and the test result showed that the thickness was about 3.2μm. The finished product was subjected to 48-hour salt spray and 48-hour artificial sweat tests, and there was no corrosion on the surface after the tests. The finished product was subjected to a wear resistance test in a vibration plate, and when the standard sample placed at the same time as the finished product was worn away by 5.6mg, the finished product had no obvious bottom exposure and discoloration.

[0080] Example 3

[0081] In this embodiment, a wear-resistant, corrosion-resistant, and bio-friendly titanium oxide dark gold composite coating is sputtered on a 304 stainless steel substrate part. The specific steps are as follows:

[0082] Step S1, using a wax removal solution, an oil removal solution and deionized water in sequence to preliminarily clean the substrate in an ultrasonic cleaning device, and then blowing the substrate dry after cleaning.

[0083] Step S2, a magnetron sputtering furnace equipped with a cathode electron gun, an anode, a reaction furnace and an inert gas introduction device is used to perform secondary cleaning on the substrate that has been ultrasonically cleaned. Specifically, argon gas is introduced into the reaction furnace through the inert gas introduction device; the vacuum device is started to draw the vacuum degree in the reaction furnace to 15.0×10 -3 Pa, set the cathode electron gun current to 140A, the pulse negative bias to -500V, and the cleaning time to 10 minutes.

[0084] Step S3, in a magnetron sputtering furnace, two pure titanium cathode targets are used to deposit a base layer on the surface of the substrate. Specifically: argon gas is introduced into the reaction furnace through an inert gas introduction device; the vacuum device is started to draw the vacuum degree in the reaction furnace to 0.8 Pa, the current of the cathode electron gun is set to 19A, the pulse negative bias voltage is -80V, the sputtering time is 35 minutes, and the temperature in the reaction furnace is 150°C.

[0085] Step S4, in a magnetron sputtering furnace, a pure titanium cathode target and a pure aluminum cathode target are used to deposit a surface layer on the surface of the base layer, and argon gas is introduced into the reaction furnace through an inert gas introduction device; the vacuum pumping device is started to pump the vacuum degree in the reaction furnace to 0.2 Pa, and the current I of the cathode electron gun corresponding to the pure titanium cathode target is set. 纯钛 The current I of the cathode electron gun corresponding to the pure aluminum cathode target is 12A. 纯铝 The current was 10A, the pulse negative bias voltage was -200V, the sputtering time was 4 hours, and the temperature in the reaction furnace was 250°C.

[0086] Step S5, placing the parts with the base layer and the surface layer deposited thereon into a vacuum furnace, starting the vacuum pumping device, pumping the vacuum degree in the reaction furnace to 0.2 Pa, setting the vacuum furnace to be started and heating to 1300°C at a heating rate of 120°C / min, keeping the temperature for 1 minute, first cooling to 780°C at a cooling rate of 110°C / min, and then rapidly cooling to room temperature;

[0087] Step S6, put the parts cooled to room temperature into a heating furnace, set the air circulation rate of the heating furnace to 0.1m / s, and heat to 400°C at a heating rate of 12°C / min. After keeping warm for 45 minutes, cool with the furnace to obtain the final finished parts.

[0088] The finished product was taken out, and the surface was dark gold. The thickness of the composite coating was tested by scanning electron microscopy, and the test result showed that the thickness was about 4.1μm. The finished product was subjected to 24-hour salt spray and 24-hour artificial sweat tests, and there was no corrosion on the surface after the tests. The finished product was subjected to a wear test in a vibration plate, and when the standard sample placed at the same time as the finished product was worn away by 5.3mg, the finished product had no obvious bottom exposure and discoloration.

[0089] It is understandable that the above three embodiments use three common substrates in watch exterior parts, but the colored wear-resistant composite coating for decoration and the preparation method thereof provided by the present invention are not limited to the above three substrates.

[0090] The present invention provides a colored wear-resistant composite coating for decoration, which is composed of a base layer and a surface layer. The surface layer is TiO 2 With Al 2 O 3 The mixed oxide layer is composed of Ti. Al 2 O 3 It has high hardness, excellent wear resistance and transparency, and can significantly improve the performance of TiO 2 The wear resistance and color durability of the surface layer. The wear-resistant composite coating prepared by multi-target magnetron sputtering process not only simplifies the process flow, but also makes the coating composition easier to control. In addition, the present invention adopts a unique sintering process to form γ-TiAl and α 2 -Ti 3 The full lamellar structure of Al ensures that 2 O 3 With TiO 2 The particle size and distribution of the mixed surface layer are uniform, thus giving the oxidized composite coating an optimal appearance and excellent performance. The composite coating prepared by the scheme of the present invention has the following characteristics:

[0091] A variety of color options: The color can be adjusted according to needs to meet the needs of different application scenarios.

[0092] Excellent appearance: The coating surface is smooth and uniform with excellent visual effect.

[0093] High hardness and good bonding strength: The composition of the base layer and the surface layer is similar, ensuring that the coating is not easy to peel off or wear.

[0094] Excellent wear resistance: Al 2 O 3 The wear resistance of the surface layer is improved and the service life of the composite coating is significantly extended.

[0095] Bio-friendliness: Applicable to fields with strict requirements on biocompatibility, such as medical devices and implants.

[0096] Corrosion resistance: Excellent corrosion resistance in a variety of environments.

[0097] In summary, the composite coating provided by the present invention not only has beautiful appearance but also has high performance characteristics, and is suitable for being widely used in the field of decoration.

[0098] The above are only specific implementations of the present invention, which cannot be used to limit the scope of the present invention. Equivalent changes made by ordinary technicians in this technical field based on this creation, as well as changes known to technicians in this field, should still fall within the scope of the present invention.

Claims

1. A colored wear-resistant composite coating for decoration, characterized in that: The composite coating (20) comprises a primer layer (21) and a surface layer (22) which are sequentially formed on the surface of a substrate (10), wherein: The composition of the surface layer (22) is 41% to 48% Al2O3 by mass percentage, and the rest is TiO2; The primer layer (21) contains at least Ti, the mass percentage of which exceeds 75%.

2. The colored wear-resistant composite coating for decoration according to claim 1, characterized in that: The thickness of the surface layer (22) is 1 to 5 um.

3. The colored wear-resistant composite coating for decoration according to claim 1, characterized in that: The thickness of the base layer (21) is 0.3-1 um.

4. A method for preparing a colored wear-resistant composite coating for decoration, comprising preparing the colored wear-resistant composite coating for decoration as claimed in any one of claims 1 to 3 on the surface of a substrate, characterized in that: The method comprises the following steps: Step S1, using ultrasonic cleaning equipment to perform preliminary cleaning on the substrate, and then drying the substrate after cleaning; Step S2, loading the ultrasonically cleaned substrate into a reaction furnace of a magnetron sputtering furnace, introducing an inert gas into the reaction furnace, and performing a secondary cleaning on the substrate; Step S3, loading a first cathode target and a second cathode target in the magnetron sputtering furnace, and using the first cathode target and the second cathode target to deposit a base layer on the surface of the substrate that has been cleaned twice; the first cathode target and the second cathode target are both titanium alloys with a titanium content greater than 75%; Step S4, loading a third cathode target and a fourth cathode target in the magnetron sputtering furnace, and using the third cathode target and the fourth cathode target to deposit a surface layer on the surface of the base layer, wherein the third cathode target is pure titanium and the fourth cathode target is pure aluminum; by controlling the power applied to the third cathode target and the fourth cathode target, the mass percentage content of Al in the surface layer is 38% to 45%; Step S5, placing the substrate on which the base layer and the surface layer are deposited into a vacuum furnace, heating to a first temperature at a first heating rate after evacuation, keeping the temperature for a first time, and cooling according to a first cooling method; the first heating rate is 90°C / min to 120°C / min; the first temperature is 1200 to 1300°C, the first time is 1 to 3 minutes, and the first cooling method is first cooling to 750°C to 800°C at 80°C / min to 110°C / min, and then rapidly cooling to room temperature; Step S6, placing the substrate cooled to room temperature into a heating furnace connected to air, setting the heating furnace to allow air to flow in at a first flow rate, heating to a second temperature at a second heating rate, and then keeping the temperature for a second time and then cooling according to a second cooling method; the first flow rate is 0.01m / s~2m / s, the second heating rate is 5℃ / min~15℃ / min, the second time is 0.5~2h, and the second cooling method is cooling to room temperature with the furnace.

5. The method for preparing the colored wear-resistant composite coating for decoration according to claim 4, characterized in that: In the step S1, the preliminary cleaning includes a wax removal solution cleaning step, an oil removal solution cleaning step, and a deionized water cleaning step performed sequentially.

6. The method for preparing the colored wear-resistant composite coating for decoration according to claim 4, characterized in that: In step S2, the vacuum degree in the reaction furnace is (8.0-15.0)×10 -3 Pa, the current of the cathode electron gun is 110-150A, the pulse negative bias voltage applied to the substrate is -350-500V, the working time is 10-15 minutes, and the inert gas is argon or nitrogen.

7. The method for preparing the colored wear-resistant composite coating for decoration according to claim 4, characterized in that: In the step S3, the vacuum degree in the reaction furnace is 0.1-1 Pa, the current of the cathode electron gun of the first cathode target and the second cathode target is 10-20 A, the pulsed negative bias voltage applied to the substrate is -130--80 V, argon or nitrogen is introduced into the reaction furnace, the working time is 15-35 minutes, and the temperature in the reaction furnace does not exceed 200°C.

8. The method for preparing a colored wear-resistant composite coating for decoration according to claim 4, characterized in that: In step S4, the vacuum degree in the reaction furnace is 0.01-0.3 Pa, and the current I 纯钛 is 10-15A, the current I of the cathode electron gun of the fourth cathode target 纯铝 The pulse negative bias voltage applied to the substrate is -200 to -150 V, argon or nitrogen is introduced into the reaction furnace, the working time is 4 to 6 hours, and the temperature in the reaction furnace does not exceed 250°C.

9. The method for preparing a colored wear-resistant composite coating for decoration according to claim 4, characterized in that: In step S5, the vacuum degree in the vacuum furnace is maintained at 0.05-0.5 Pa.

10. The method for preparing a colored wear-resistant composite coating for decoration according to claim 4, characterized in that: In step S6, when the second temperature is 280°C to 330°C, a light yellow coating is obtained, when the second temperature is 370°C to 420°C, a dark gold coating is obtained, when the second temperature is 460°C to 530°C, a blue coating is obtained, when the second temperature is 570°C to 620°C, a green coating is obtained, and when the second temperature is 650°C to 690°C, a purple coating is obtained.